2017
DOI: 10.1002/14651858.cd011767.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Genomics-based non-invasive prenatal testing for detection of fetal chromosomal aneuploidy in pregnant women

Abstract: These results show that MPSS and TMPS perform similarly in terms of clinical sensitivity and specificity for the detection of fetal T31, T18, T13 and sex chromosome aneuploidy (SCA). However, no study compared the two approaches head-to-head in the same cohort of patients. The accuracy of gNIPT as a prenatal screening test has been mainly evaluated as a second-tier screening test to identify pregnancies at very low risk of fetal aneuploidies (T21, T18 and T13), thus avoiding invasive procedures. Genomics-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 289 publications
4
68
0
1
Order By: Relevance
“…[18]. The cfDNA is a popular paid service in Taiwan [10,19] because it can be used as early as 10 weeks pregnancy, and has a high sensitivity (99.3%) and specificity (99.8%) for Trisomy 21, no risk of miscarriage, and a clinical sensitivity of 90.9%, 65.0% for Trisomy 18 and Trisomy 13, respectively [20,21]. It is not known if women are aware of the development of novel genetic screening tests.…”
Section: Introductionmentioning
confidence: 99%
“…[18]. The cfDNA is a popular paid service in Taiwan [10,19] because it can be used as early as 10 weeks pregnancy, and has a high sensitivity (99.3%) and specificity (99.8%) for Trisomy 21, no risk of miscarriage, and a clinical sensitivity of 90.9%, 65.0% for Trisomy 18 and Trisomy 13, respectively [20,21]. It is not known if women are aware of the development of novel genetic screening tests.…”
Section: Introductionmentioning
confidence: 99%
“…This study identified that nearly half of those surveyed believed that a FFA could always be picked up at a 12‐week ultrasound scan while a greater amount believed a FFA diagnosis could always be given at the 20 to 22‐week ultrasound scan. While prenatal diagnosis within the first trimester has advanced, a FFA diagnosis will not always be given during this time. Those surveyed were unaware that while a diagnosis is possible at any time, prenatal diagnosis is dependent upon availability of equipment, skills, and experience .…”
Section: Discussionmentioning
confidence: 99%
“…Where there was no heterogeneity in either sensitivity or specificity, meta‐analysis cannot calculate confidence intervals (CIs). In this case, we followed the methods of the 2017 Cochrane review to sum all of the studies and calculate CIs using the Wilson method …”
Section: Methodsmentioning
confidence: 99%
“…Three main cfDNA testing strategies had been used for trisomy screening, which all rely on next‐generation sequencing (NGS) to quantify cfDNA: random whole‐genome sequencing, targeted sequencing of selected nonpolymorphic regions (digital analysis of selected regions, DANSR), or targeted sequencing of single‐nucleotide polymorphisms. Systematic reviews have suggested that NGS‐based cfDNA strategies have a high sensitivity and specificity for detecting trisomy 21 (T21), trisomy 18 (T18), and trisomy 13 (T13) . However, most of the identified studies were prone to bias, especially in terms of the selection of participants and study flow and timing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation